Integrated Aquaculture within Agriculture Irrigation for Food Security and Adaptation to Climate Change - Gurung, Tek Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
In the existing complexities of climate change, biodiversity, subsistence farming and several other issues associated with agriculture production, gaining self sufficiency in food security is challenging. Experiences from many countries suggest that aquaculture integration within agricultural irrigation, where aquaculture is a non-consumptive user of water, has contributed to increase overall productivity. Irrigation purposively provides water for agriculture in other than rain fed conditions. Strategically, however, irrigation should lead to efficient water management for increased agricultural production especially in present context of biodiversity loss, poverty, water, food and nutritional insecurity in the era of climate change. To overcome the problems of food security and many other relevant issues, the integration of aquaculture within agriculture irrigation is highly recommended. DOI: http://dx.doi.org/10.3126/hn.v11i1.7214 Hydro Nepal Special Issue: Conference Proceedings 2012 pp.73-77